The Effectiveness Of Soursop Leaf Decoction On Decreasing Uric Acid Levels At Adow Health Centre - Dian P Iman; Kristine Dareda; Bella Vista Datunsolang (Sean Institute, 2023)
The Excessive of uric acid levels can cause the sedimentation process of uric acid crystals it can cause the gout. The antioxidant in soursop leaves is effective to slowdown and also prevent the gout. The purpose of this study is to find out the effect of soursop leaf decoction on reducing uric acid levels in the work area at UPTD Adow Health Centre. The research method use the Quasy Experiment, with a one group pre-post test method . The samples in this study taken 15 respondents by the total sampling techniques. The research instruments use an uric acid level checking and observation sheets. Then the data collected processed by Friedman's Statistical Test. Findings , the friedman statistical test results obtained a p value = 0.001 with a significance of < 0.05. The conclusion is giving soursop leaf decoction is effective on reducing uric acid levels in the working area at UPTD Adow Health Centre. It is hoped the decoction of soursop leaf can be useful as alternative medicine to lower the uric acid levels.